1993
DOI: 10.1111/j.1528-1157.1993.tb02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Manifestations of Long‐Term Valproate Therapy

Abstract: Sixty patients receiving long-term valproate (VPA) monotherapy were studied for hematologic side effects. All were patients in a long-term care facility and ranged in age from 2 to 29 years (mean 14.6 years). Twenty developed at least one prominent hematologic abnormality. Thrombocytopenia and macrocytosis were the most common findings. In patients with macrocytosis, platelet counts were inversely related to VPA levels. Serum B12 levels were increased in 51 of the patients. In 12 patients with macrocytosis who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 17 publications
3
42
1
5
Order By: Relevance
“…Many of these toxicities appear to be dose-related [5]. Twenty of 60 patients treated with valproic acid were reported to have significant hematological abnormalities, with thrombocytopenia and macrocytosis being the most common [6]. Serious, but reversible, hematologic toxicity resembling a myelodysplastic syndrome (MDS) has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these toxicities appear to be dose-related [5]. Twenty of 60 patients treated with valproic acid were reported to have significant hematological abnormalities, with thrombocytopenia and macrocytosis being the most common [6]. Serious, but reversible, hematologic toxicity resembling a myelodysplastic syndrome (MDS) has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This problem arises, in part, because therapeutic blood levels are statistical best estimates of the AED levels that produce toxic effects and are often derived from small samples of patients. Even adverse effects that do not seem directly related to the antiepileptic effect of an AED, such as thrombocytopenia with valproate treatment, are dose related (38). Dose-related adverse effects also often increase when multiple AEDs are combined.…”
Section: Rapid Dose Changes High Aed Doses Polypharmacy and Other mentioning
confidence: 99%
“…3 Thrombocytopenia is one of the most common side effects associated with VPA therapy, with incidence ranging from 1% to 30%. 4,5 It is mild to transient in most cases which usually resolves spontaneously on dosage reduction or withdrawal of the drug. 6,7 Available reports showed that thrombocytopenia associated with VPA therapy has been reported to resolve without interruption of VPA treatment 8 and has also been reported to endure over time or to have an erratic course.…”
Section: Introductionmentioning
confidence: 99%